2022
DOI: 10.3390/polym14061070
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Transparent and Uniform Cellulose/Polyethylene Composite Films from Used Disposable Paper Cups by the “One-Pot Method”

Abstract: Disposable paper cups are usually composed of high-grade paper board and an inner polyethylene coatings and are extensively used in daily life. However, most disposable paper cups are only used for a short time and then incinerated or accumulated in landfill at the end of their service due to the difficulty in separating the components, leading to a serious threat to our ecosystem. Therefore, developing a facile and green method to recycle and reuse disposable paper cups is vital. By using ionic liquid 1-allyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
(103 reference statements)
1
9
0
Order By: Relevance
“…Meanwhile, the absorption peak at around 899 cm –1 is weak for the CPs, while it enhanced intensely for the regenerated films. All the above phenomena indicate the changes of hydrogen bonds and the transition of cellulose from I to II phase after regeneration, which is in correspondence with our former results. Additionally, PMIA short fibers demonstrate peaks at approximately 1654, 1608, and 1538 cm –1 , assigned to the vibration of the CO (amide) stretching, aromatic ring stretching, and −NH– bending, which are characteristic peaks for the PMIA structure. , Taking the −NH– bending vibration (1538 cm –1 ) and aromatic ring stretching vibration (1608 cm –1 ) as references, it can be concluded that these two peaks are enhanced obviously with more content of PMIA, indicating the successful and homogeneous incorporation of PMIA into the cellulose matrix, which is important to the property of the cellulose/PMIA composite films.…”
Section: Resultssupporting
confidence: 88%
“…Meanwhile, the absorption peak at around 899 cm –1 is weak for the CPs, while it enhanced intensely for the regenerated films. All the above phenomena indicate the changes of hydrogen bonds and the transition of cellulose from I to II phase after regeneration, which is in correspondence with our former results. Additionally, PMIA short fibers demonstrate peaks at approximately 1654, 1608, and 1538 cm –1 , assigned to the vibration of the CO (amide) stretching, aromatic ring stretching, and −NH– bending, which are characteristic peaks for the PMIA structure. , Taking the −NH– bending vibration (1538 cm –1 ) and aromatic ring stretching vibration (1608 cm –1 ) as references, it can be concluded that these two peaks are enhanced obviously with more content of PMIA, indicating the successful and homogeneous incorporation of PMIA into the cellulose matrix, which is important to the property of the cellulose/PMIA composite films.…”
Section: Resultssupporting
confidence: 88%
“…X-ray diffractometer D8 AD-VANCE purchased from the Bruker, Ettlingen, Germany in reflection mode with CuKa (λ = 1.5406 Å) radiation was employed to record the X-ray diffractograms (XRD) of raw materials (P-OCTs and GSEs) and the regenerated cellulose/GSEs films (CGSEs 0, CGSEs 0.25, CGSEs 0.5, CGSEs 1.0 and CGSEs 2.0), in which 40 kV, 40 mA, 20 °/min and 2θ span ranging from 5° to 60° were preset for all samples [ 45 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…OCA 50 machine purchased from Dataphysics, Filderstadt, Germany was employed to record the surface hydrophilicity of CGSEs 0, CGSEs 0.25, CGSEs 0.5, CGSEs 1.0 and CGSEs 2.0. More than five positions were recorded and the averaged contact-angle values were displayed in this work [ 45 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, heat transfer in the building is related to how fast or slow the interior temperatures reach the exterior temperature. Researchers are interested in developing composite materials with natural fibers, which generate thermal lag when combined with thermal inertia [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%